Reformas en educación superior. Aspectos y perspectivas / Reforms in higher education. Aspects and views (2011)
Este artículo examina algunos de los cambios recientes de la educación superior en América Latina: internacionalización, diversificación de instituciones y de ofertas educativas y privatización-mercantilización. Presenta distintas actitudes frente a estos cambios. Considera las reformas curriculares de los 90, tomando el ejemplo de la Universidad Nacional de Colombia. Finalmente retoma como elementos básicos del carácter de la Universidad Pública su opción por lo público, lo estratégico, el largo plazo y el interés general. / Abstract. This paper considers some of the recent changes in higher education in Latin American such as internationalisation, diversification of institutions and educational offer, and privatisation- commercialization. It presents different attitudes towards these changes. It also considers the curricular reforms of the 1990’s, following the example of the National University of Colombia. Finally it retakes, as basic elements of the nature of the Public University, the emphasis on public, strategic, long-term and general interest.